Analysis of the Santri-Friendly Pesantren Policy in Preventing Violence Cases at Pesantren Ar-Risalah Bantul - Lilik Setyawan (Early Publishing, 2026)
This research aims to examine how the pesantren policies that are friendly toward students are implemented in efforts to prevent cases of violence at Pesantren Ar-Risalah Bantul. This research emerged because more and more people care about the protection of students' rights and because there are many cases of violence in Islamic boarding schools. Therefore, it is important to have educational policies that are safe, humane, and free from physical, verbal, or psychological violence. This research uses a qualitative approach with a case study method. Data were obtained thru interviews, observations, and recordings involving the head of the pesantren, caregivers, teachers, and students. Data analysis was conducted descriptively using the policy implementation model from Van Meter and Van Horn, as well as the model from Merilee S. Grindle, and the AGIL theory by Talcott Parsons. The research results show that the pesantren's policies supporting students are implemented by creating rules against violence, a system for reporting cases, 24-hour dormitory supervision, training for educators on child-friendly education, and strengthening character education based on Islamic values. Violence prevention is carried out by teaching peace, mentoring the students, disseminating information about anti-bullying, and actively involving the pesantren administrators. The policy has a positive impact on creating a safer, more comfortable, and supportive atmosphere in the pesantren, as well as reducing the likelihood of physical, verbal, and psychological violence. The limitation of this research is its focus on only one pesantren located in a developing area, where there are limitations in technology and digital monitoring systems. This research offers something new by combining policy implementation theory and educational sociology approaches to create a pesantren model that is friendly to students, humanistic, and sustainable.